Lung Ultrasound and Caval Indices to Assess Volume Status in Maintenance Hemodialysis Patients - Mujtaba Z. AL-Saray; Ala Ali (POCUS Journal, 2023)
Background: Volume overload is common in end stage kidney disease (ESKD) and dialysis patients. Hence, the need for objective tools to detect such volume excess. Point of care ultrasound (POCUS) is a goal-directed, bedside examination to answer such a specific diagnostic question. Methods: One hundred Iraqi adult hemodialysis patients were recruited from February 1 to May 31, 2022. Primary clinical, dialysis data, and prescriptions were recorded. A nephrologist performed a POCUS examination after the last dialysis session of the week. In addition, an ultrasound examination of the chest was performed to detect B-lines and pleural effusion. Caval parameters included inferior vena cava (IVC) diameter and collapsibility index.  Results: The mean age of the study group was 51.48 ± 14.6 years, with 53% males. The mean interdialytic weight gain was 2.74 ± 1.15 Kg. Lower limb edema and pleural effusion were present in 33% and 27%, respectively. Forty-seven percent of patients had >3 B-lines on lung ultrasound with a range of 12. Forty-three percent of patients had an IVC diameter of >2 cm, and 93% had <50% IVC collapsibility. In total, 97% of patients had evidence of excess volume by ultrasound criteria. IVC collapsibility index was the most prevalent sign of excess volume (93%). Patients without lower limb edema and pleural effusion had positive B-lines in 38.8% and 38.3%, an IVC diameter >2 cm in 46.2% and 38.3%, and IVC collapsibility <50% in 89.5% and 95.8% respectively.  Conclusion: Iraqi maintenance hemodialysis patients are volume overloaded, which warrants proper intervention for detection and dialysis management. POCUS is a useful and easily performed technique to assess the volume status.